Can We Mention About an Idea Called “Abstract Symbolic Style” in Turkish Art? - Yunus Aslan (Art-Sanat)
Symbols play a crucial role in various domains, serving as conveyors of meaning through concrete signs with abstract significance. In some periods, it is seen that certain symbols stand out uniquely to that period and some symbols are used repeatedly or transformed throughout history. It is very difficult to reach definite conclusions about the origin of symbols in the history of art. However, the external and internal factors that influence the art, of course, shape the symbols that the work contains, as well as the work. A work of art, which is the product of a collective process is affected by many conditions such as the social environment, economy, material supply, geographical variables, the government, the wishes of the administrator and the artist, the understanding and style of art of the period, religion and sacred elements, the artist’s experience and inner world. The work, which is formed by selection among all these variables is a cornerstone of the general art style. Anatolian Medieval art can be interpreted as the art of societies, not the art of individuals like modern art. In this respect, in Turkish art and symbolism, where the state, religion and social powers come to the fore, these mentioned elements appear as the dominant and guiding power. Should the idea of “abstract symbolic style” be mentioned in Turkish art? Which factors influenced art and style? What is the place of stamps in the transformation of ancient symbols into art? In this study, answers to these questions and problems are sought.